Role of Sex Hormones on Brain Mitochondrial Function, with Special Reference to Aging and Neurodegenerative Diseases - Gaignard, Pauline; Liere, Philippe; Thérond, Patrice; Schumacher, Michael; Slama, Abdelhamid; Guennoun, Rachida (Frontiers in Aging Neuroscience, 2017)
The mitochondria have a fundamental role in both cellular energy supply and oxidative stress regulation and are target of the effects of sex steroids, particularly the neuroprotective ones. Aging is associated with a decline in the levels of different steroid hormones, and this decrease may underline some neural dysfunctions. Besides, modifications in mitochondrial functions associated with aging processes are also well documented. In this review, we will discuss studies that describe the modifications of brain mitochondrial function and of steroid levels associated with physiological aging and with neurodegenerative diseases. A special emphasis will be placed on describing and discussing our recent findings concerning the concomitant study of mitochondrial function (oxidative phosphorylation, oxidative stress) and brain steroid levels in both young (3-month-old) and aged (20-month-old) male and female mice.